2022
DOI: 10.1002/anie.202114423
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Ultrafast Proton Rocking in the BLUF Domain

Abstract: We present direct observation of ultrafast proton rocking in the central motif of a BLUF domain protein scaffold. The mutant design has taken consideration of modulating the proton‐coupled electron transfer (PCET) driving forces by replacing Tyr in the original motif with Trp, in order to remove the interference of a competing electron transfer pathway. Using femtosecond pump–probe spectroscopy and detailed kinetics analysis, we resolved an electron‐transfer‐coupled Grotthuss‐type forward and reverse proton ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(46 citation statements)
references
References 42 publications
7
39
0
Order By: Relevance
“…S3 ) ( 31 ). Most interestingly, in comparison with the FMNH˙/W˙ SADS of our recently reported Y6W/W90F mutant which is a W analog of WT ( 37 ), we discover clear spectral signatures of YO˙ ( 38 , 39 ) around 410 nm to 420 nm for WT, which is also observed in the Q48A and Q48E mutants ( SI Appendix , Fig. S10 ).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…S3 ) ( 31 ). Most interestingly, in comparison with the FMNH˙/W˙ SADS of our recently reported Y6W/W90F mutant which is a W analog of WT ( 37 ), we discover clear spectral signatures of YO˙ ( 38 , 39 ) around 410 nm to 420 nm for WT, which is also observed in the Q48A and Q48E mutants ( SI Appendix , Fig. S10 ).…”
Section: Resultssupporting
confidence: 60%
“…4 A and C ) show typical characteristics of FMN* for flavoproteins ( SI Appendix , Fig. S3 ) ( 37 ). The blue SADS component has positive broad absorptions in 500 nm to 650 nm and a negative peak at 384 nm that are attributed to FMNH˙ ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The role of proton transfer in the function of OaPAC BLUF was examined in a recent paper by the Zhong group where the authors replaced the tyrosine by a tryptophan (Y6W). 48 Kang et al observed a sequential electron transfer process: formation of the flavin anionic radical, followed by the formation of the neutral semiquinone. The authors proposed that they observed proton rocking in which the tryptophan transiently donated a proton to the flavin to form the neutral semiquinone followed by a reverse PT; the rates of the forward and reverse PT were very close, being 51 ps and 52 ps, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The role of proton transfer in the function of OaPAC BLUF was examined in a recent paper by the Zhong group where the authors replaced the tyrosine by a tryptophan (Y6W) . Kang et al observed a sequential electron transfer process: formation of the flavin anionic radical, followed by the formation of the neutral semiquinone.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of further signal transduction to acceptor proteins are not completely clear. The reverse process of electron transfer to tyrosine (PCET) leads to the restoration of the original form of the photoreceptor and the closure of the photocycle [ 227 , 228 , 229 , 230 , 231 ].…”
Section: Biochemical and Physiological Application Of Pterin Photoche...mentioning
confidence: 99%